Determinan Self-Efficacy terhadap Job Satisfaction melalui Work Engagement pada Karyawan PT. Asuransi - Utama, Rony Edward; Nor Lailla, Nor Lailla; Tarmizi, M. Irfan; Chudri, Intan Rizkia (Business and Entrepreneurial Review, 2023)
This research aims to determine the influence of self-efficacy on job satisfaction through work involvement. This research uses a quantitative approach, the sample was selected using a sampling technique, namely Purposive Sampling. The sample used was 100 insurance employees. Structural Equation Modeling is used to process data that has been collected using the help of the SmartPLS application. The research results show that: (1) Self-efficacy has a significant effect on employee job satisfaction; (2) Self-efficacy has a positive and significant effect on employee work engagement; (3) Work engagement has a significant positive effect on employee job satisfaction. The level of work engagement among PT Asuransi employees can be said to be good in increasing the job satisfaction of each employee; (4) work involvement mediates the influence of self-efficacy on job satisfaction. Job satisfaction is influenced by self-efficacy for each person in the organization